Quasi one-dimensional band dispersion and surface metallization in long-range ordered polymeric wires - Guillaume Vasseur (Nature Portfolio, 2016)
Polymerization on surfaces is an emerging approach for producing graphene nanoribbons with a tunable bandgap, a promising material for carbon-based electronics. Here, Vasseur et al.show quasi-one-dimensional band structure of a model semiconducting polymer synthesized directly on a supporting surface.